2023
DOI: 10.1007/s11904-023-00662-0
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Impact of Depot Medroxyprogesterone Acetate on Vaginal Mucosal Endpoints and Relevance to Sexually Transmitted Infections

Abstract: Purpose of Review The long-acting reversible intramuscularly-injected contraceptive depot medroxyprogesterone acetate (DMPA-IM) is widely used by cisgender women in Africa. Although DMPA-IM provides reliable contraception, potential effects on the female genital tract (FGT) mucosa have raised concern, including risk of HIV infection. This review summarises and compares evidence from observational cohort studies and the randomised Evidence for Contraceptive Options in HIV Outcomes (ECHO) Trial. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
(23 reference statements)
0
0
0
Order By: Relevance
“…This population also experiences high rates of often-unplanned pregnancies and needs access to safe and effective contraceptives. However, adolescents have been severely under-represented in studies focusing on contraceptives and HIV risk [ 2 , 3 ].The few existing studies that do include adolescents have demonstrated a distinct physiological and immunological microenvironment in adolescent genital tract, emphasizing the need for evaluation of contraceptive use and risk of HIV/STI acquisition in this population [ 4 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This population also experiences high rates of often-unplanned pregnancies and needs access to safe and effective contraceptives. However, adolescents have been severely under-represented in studies focusing on contraceptives and HIV risk [ 2 , 3 ].The few existing studies that do include adolescents have demonstrated a distinct physiological and immunological microenvironment in adolescent genital tract, emphasizing the need for evaluation of contraceptive use and risk of HIV/STI acquisition in this population [ 4 9 ].…”
Section: Introductionmentioning
confidence: 99%